First macrofaunal evidence in the Devonian Codo Formation from Argentina and insights into the youngest calmoniid trilobite records - Rustán, Juan José (2025)
We report the discovery of macrofauna in the Devonian Codo Formation, from the Precordillera of the San Juan Province, Argentina, based on a poorly preserved calmoniid trilobite. The cephalic remains resemble Punillaspis argentina previously reported in the late Givetian Chigua Formation, considered the lateral equivalent of the Codo Formation to the north. However, the thorax most closely resembles acastomorph calmoniids like Pennaia and relatives, widely distributed in the Early and Middle Devonian of Southwestern Gondwana (Malvinoxhosanic = Malvinokaffric Realm). Taking into account previous palynological evidence and the youngest stratigraphic records of calmoniid trilobites, the evidence supports most probably late Givetian age for the Codo Formation.